Detection of facial areas in thermal images - Kolářová, Dana; Bernard, Vladan (Lékař a technika, 2015)
This article deals with non-contact measurement of temperature in a human faces and describes program for the evaluation of temperature changes. It describes the algorithm of the program, the possibility of using and further deals with the possibilities of the segmentation of thermal images. Variety of image processing methods were used to design this algorithm including registration of images, segmentation using k-means clustering, Hough transformation, thresholding and others. The aim is to distinguish a human face from the hair and background. It also describes the possibility of detection of individual facial details. The functionality of those procedures was tested on experimental data.
Keywords: registrace obrazu; bezkontaktní měření teploty; výzkum; segmentace obrazu; obličej; software; Humans; Diagnostic Imaging; Face; Thermometry; termometrie; Research; Software; tělesná teplota; termokamera; lidé; Body Temperature; diagnostické zobrazování